Genetic modulation of anemia severity, hemolysis level, and hospitalization rate in Angolan children with sickle cell anemia - Germano, Isabel (2022)
Background: Sickle Cell Anemia (SCA) is a genetic disease caused by the c.20 A > T mutation in the HBB gene, generally characterized by sickle erythrocytes, chronic hemolytic anemia, and vaso-occlusive events. This study aimed to investigate genetic modulators of anemia severity, chronic hemolytic rate, and clinical manifestations in pediatric SCA patients from Angola, where the disease is a severe public health problem. Methods and Results: The study was conducted on 200 SCA children living in Luanda or Caxito province. Their clinical phenotype was collected from patients' hospital records. Hematological and biochemical phenotypes were characterized in steady-state conditions. Twelve polymorphic regions in VCAM1, CD36, and NOS3 genes were genotyped using PCR, RFLP, and Sanger sequencing. CD36 gene promoter variants showed a significant impact on anemia severity. Particularly, the rs1413661_C allele was associated with lower hemoglobin levels and an increased number of hospitalizations and transfusions. This is the first report associating this SNP with SCA phenotypic heterogeneity. Moreover, the rs1041163_C allele in VCAM1 was associated with lower LDH levels; inversely the rs2070744_C allele in NOS3 was related to higher LDH levels and a number of hospitalizations, being a risk factor for increased hemolytic rate. Conclusion: This study highlights, for the first time in the Angolan population, the importance of the genetic modifiers of vascular cell adhesion and nitric oxide metabolism in SCA pediatric phenotypic variability.